The Effect of Aggregate Gradation Variation on Mechanical Performance and Porosity of Porous Geopolymer Concrete - Saputro, Yayan Adi; Qomaruddin, Mochammad; Budianta, Tarsisius Dwi Wibawa (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Porous geopolymer concrete has gained attention as a sustainable and environmentally friendly alternative to conventional Portland cement-based concrete, utilizing industrial waste such as fly ash. This study investigates the effect of aggregate gradation variations on the mechanical properties, porosity, and sustainability of fly ash-based porous geopolymer concrete. The experimental method was employed, utilizing fly ash as the primary binder, sodium hydroxide (NaOH) as the activator, and coarse aggregates of varying sizes (3/8